Effect of Financial Literacy and Fintech Payment of Financial Management Behavior with Internal Locus of Control as Moderator - Hidayati, Aulia Riska; Nugroho, Dwiyanjana Santyo (PT. Riset Press International, 2023)
This study examines private university students in West Jakarta which aims to determine the effect of financial literacy and fintech payments on financial management behavior with internal locus of control as a moderator variable. The dependent variables used are financial literacy and fintech payments. The analysis of this study used multiple linear regression with SPSS 27 (Statistical Package for Social Science). The results of this study indicate that: (a) financial literacy influences financial management behavior; (b) fintech payments affect financial management behavior; (c) internal locus of control strengthens the relationship between financial literacy and financial management behavior; (d) the internal locus of control strengthens the relationship between fintech payments and financial management behavior. Keywords:financial literacy, fintech payments, financial management behavior, locus of control